Peran Pemerintah Desa Dalam Penerapan Protokol Kesehatan Berbasis Kelompok Masyarakat Di Desa Wantisari, Berdasarkan Peraturan Bupati Nomor 28 Tahun 2020 - Dzikri Amarullah (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
The village government has the authority and policy in handling COVID-19. As the village frontline, we have a very important role in controlling COVID-19. Wantisari Village, as one of the villages in Lebak Regency, should take strategic steps in implementing health protocols and adapting new habits at the village level. However, the actualization of health protocols in Wantisari Village has not run optimally, it can be proven by the presence of nineteen positive cases in Wantisari Village. Based on this background, the researcher will discuss about the role of the Wantisari village government in implementing health protocols and how to enforce law in implementing health protocols? The research method used is empirical juridical with qualitative juridical data analysis sourced from primary data based on field research in wantisari village and primary legal materials as a form of literature study based on the provisions of the Lebak regent regulation number 28 of 2020. Based on the results of the study, the authority of the wantisari village government based on the regent's regulation number 28 of 2020 has carried out several efforts in implementing health protocols. This is evidenced by the existence of several village government programs such as the establishment of a village Covid-19 task force, a tough village program, regular routine raids, and various law enforcement. However, the lack of information distribution to all community groups makes the level of community compliance with health protocols very minimal. There needs to be optimization in law enforcement by the Wantisari village government. Community participation is very much needed in terms of implementing health protocols, the community needs to work together and help each other so that the Wantisari village is protected from COVID-19.